Art as an Investment: The Market for Modern Prints - Pesando, James E. (American Economic Review, 1993)
Repeat sales of modern prints at auction are used to estimate a semiannual index of prices for the period 1977-1992. As in other studies of art as an investment, prints do not compare favorably to traditional financial assets. There is substantial noise in auction prices, but little or no support for the proposition that some artists command higher prices in certain countries or that masterpieces outperform the market. One puzzle is the continuing tendency for prices realized at certain auction houses to exceed those realized at others: notably, at Sotheby's relative to Christie's in New York.